Study of the amino acid profile of alternative proteins (Helix pomatia, Lissachatina fulica, Helix aspersa) and their potential application in a healthy diet: optimization of a modern brandade recipe - Helikh, Anna; Filon, Andrii (Technology audit and production reserves, 2025)
Integrating traditional European cuisine with alternative protein sources can strengthen food security and provide the population with healthy food. Previous scientific works indicate the nutritional and environmental potential of alternative proteins. However, there is a research gap regarding their practical integration into authentic European recipes to improve nutritional value, sensory characteristics, and promote healthy eating. This study focuses on the problem of improving cod brandade for healthy nutrition. One of the problematic aspects of traditional brandade is its high fat content, limited protein content, and the use of predatory fish. This raises questions about its compliance with healthy eating principles. The object of the study is the recipe and quality of cod brandade and its modifications with alternative protein. Four samples were developed using salted semi-finished products: A0 (control Gadus morhua), A1 (Helix pomatia), A2 (Lissachatina fulica), A3 (Helix aspersa), and four samples using salted and cooked semi-finished products (50 % w/w): F0 (control Gadus morhua), F1 (Helix pomatia), F2 (Lissachatina fulica), F3 (Helix aspersa). In the experimental samples, olive oil was replaced with pumpkin seed cake protein isolate (50 % w/w). Among the snails, the highest amount of essential amino acids was found in Helix pomatia (8.39 g/100 g), although this was 23.72 % lower than the control. The protein from the Helix pomatia sample had the highest potential biological value (87.01 %), which was 3.85 % higher than the control. The chemical composition of the brandade changes significantly. The control sample (A0) is distinguished by a higher fat content, having the highest value at 29.96 %, which is 14.46 % more than A1. Samples with snails have a higher protein content, with A1 having the highest at 35.20 %, which is 15.86 % more than A0. Sample A1 achieved the highest sensory score of 8.6, surpassing A0 by 0.4 points. Texture and emulsion homogeneity indicators were better in the experimental samples due to the protein isolate. The obtained results highlight the significant potential of using alternative proteins for modernizing European cuisine and creating innovative food products for healthy nutrition.